TELAAH KRITIS PENGATURAN TENTANG YAYASAN DI INDONESIA - Fitriani Jamaluddin (MADDIKA : Journal of Islamic Family Law, 2020)
The purpose of this study is to examine  Law  No.  16  of  2001  concerning Foundations in conjunction with  Law  No.  28  of  2004  concerning  Foundations. The results showed that the basic purpose of establishing the foundation for social,  humanitarian,  and religious interests in implementation was not in accordance with the provisions of the Foundation Law, besides that there was no sanction for Foundation organs that took advantage of personal interests in the management of the Foundation.